Exploring the multifactorial nature of autism through computational systems biology: Calcium and the Rho GTPase RAC1 under the spotlight - Zeidán-Chuliá, Fares; Rybarczyk-Filho, José Luiz [UNESP]; Salmina, Alla B.; De Oliveira, Ben-Hur Neves; Noda, Mami; Moreira, José Cláudio F. (Springer Nature, 2013)
Autism is a neurodevelopmental disorder characterized by impaired social interaction and communication accompanied with repetitive behavioral patterns and unusual stereotyped interests. Autism is considered a highly heterogeneous disorder with diverse putative causes and associated factors giving rise to variable ranges of symptomatology. Incidence seems to be increasing with time, while the underlying pathophysiological mechanisms remain virtually uncharacterized (or unknown). By systematic review of the literature and a systems biology approach, our aims were to examine the multifactorial nature of autism with its broad range of severity, to ascertain the predominant biological processes, cellular components, and molecular functions integral to the disorder, and finally, to elucidate the most central contributions (genetic and/or environmental) in silico. With this goal, we developed an integrative network model for gene-environment interactions (GENVI model) where calcium (Ca2+) was shown to be its most relevant node. Moreover, considering the present data from our systems biology approach together with the results from the differential gene expression analysis of cerebellar samples from autistic patients, we believe that RAC1, in particular, and the RHO family of GTPases, in general, could play a critical role in the neuropathological events associated with autism. © 2013 Springer Science+Business Media New York.
Keywords: Autism spectrum disorders; Gene expression; In silico model; Polymorphism; Xenobiotic; calcium; protein Cdc42; Rac protein; Rac1 protein; RhoA guanine nucleotide binding protein; actin filament; autism; calcium signaling; cerebellum; environmental stress; gene expression; genetic susceptibility; genotype environment interaction; human; macroglia; microarray analysis; nerve cell plasticity; priority journal; review; systematic review; systems biology